Association between nap time, nighttime sleep, and multimorbidity in Chinese older adults: a cross-sectional study - Yanliqing Song; Lin Chen; Yue Liu (BMC Geriatrics, 2025)
Abstract Objective This study aims to explore the relationship between sleep duration and multimorbidity among elderly Chinese and to determine the optimal sleep duration for preventing multimorbidity. Methods This study is based on data from the 2020 China Health and Elderly Care Longitudinal Survey (CHARLS), which collected detailed information from 5,761elderly individuals, including demographic characteristics, sleep duration, health status, and lifestyle information. Logistic regression models were used to investigate the relationship between sleep duration and multimorbidity, and restricted cubic spline analysis was employed to analyze the dose-response relationship between sleep duration and multimorbidity. Results After adjusting for potential confounders, a U-shaped association was found between nighttime sleep duration and the likelihood of multimorbidity among the elderly. Specifically, elderly individuals with a nighttime sleep duration of 7 h had the lowest incidence of multimorbidity. Compared to those with 6–8 h of nighttime sleep, elderly individuals with less than 6 h (OR = 1.24, 95% CI: 1.05–1.48) or more than 8 h (OR = 1.79, 95% CI: 1.37–2.34) of nighttime sleep had a 24% and 79% increased likelihood of multimorbidity, respectively. The restricted cubic spline analysis further confirmed this U-shaped relationship, showing that the likelihood of multimorbidity gradually decreased as sleep duration increased from 6 to 7 h, but gradually increased as sleep duration exceeded 7 h. Additionally, a positive correlation was found between napping habits and the likelihood of multimorbidity, with elderly individuals without napping habits having a lower likelihood of multimorbidity compared to those with napping habits. Subgroup analysis indicated no significant differences in the impact of 6–8 h of nighttime sleep on multimorbidity among male and female elderly individuals and different age groups. Conclusion Appropriate nighttime sleep duration may be an important factor in preventing multimorbidity among the elderly, while increased napping duration may increase the likelihood of multimorbidity. These findings provide scientific evidence for sleep health management among the elderly, suggesting the promotion of appropriate sleep duration to reduce the likelihood of multimorbidity in this population.